2021
DOI: 10.35799/jbl.v11i2.35663
|View full text |Cite
|
Sign up to set email alerts
|

Uji Efek Imunumodulator Vco (Virgin Coconut Oil) Pada Tikus Jantan

Abstract: (Article History: Received August 25, 2021; Revised Sept 17, 2021; Accepted Sept 20, 2021) ABSTRAKVirgin coconut oil merupakan minyak kelapa murni.VCO mengandung Medium Chain Fatty Acid (MCFA) yang memiliki pengaruh dalam meningkatkan sistem imunitas. Penelitian ini bertujuan untuk menguji efek imunomodulator VCO terhadap aktivitas fagositosis dan nilai titer antibodi pada tikus jantan. Kelompok uji bersihan karbon dibagi menjadi 5 kelompok dengan masing-masing terdiri dari 5 tikus yaitu kelompok suspensi CMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Intake of VCO which contains bioactive compounds, including polyphenols, tocopherols and tocotrienols and is rich in monolaurin is known to modulate the inflammatory process and is immunomodulatory. The results of research conducted by Sebayang & Hasibuan (2021) reported that VCO has an immunomodulatory effect on increasing phagocytosis. Giving VCO to a group of experimental animals at a dose of 15 ml/kgBW/day for 14 days was proven to increase immune cell antibody titers and phagocytic activity more strongly than doses of 5 ml/kgBW and 10 ml/kgBW (Sebayang & Hasibuan, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intake of VCO which contains bioactive compounds, including polyphenols, tocopherols and tocotrienols and is rich in monolaurin is known to modulate the inflammatory process and is immunomodulatory. The results of research conducted by Sebayang & Hasibuan (2021) reported that VCO has an immunomodulatory effect on increasing phagocytosis. Giving VCO to a group of experimental animals at a dose of 15 ml/kgBW/day for 14 days was proven to increase immune cell antibody titers and phagocytic activity more strongly than doses of 5 ml/kgBW and 10 ml/kgBW (Sebayang & Hasibuan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results of research conducted by Sebayang & Hasibuan (2021) reported that VCO has an immunomodulatory effect on increasing phagocytosis. Giving VCO to a group of experimental animals at a dose of 15 ml/kgBW/day for 14 days was proven to increase immune cell antibody titers and phagocytic activity more strongly than doses of 5 ml/kgBW and 10 ml/kgBW (Sebayang & Hasibuan, 2021). Other research also states that VCO has anti-inflammatory, antioxidant and immunostimulant properties.…”
Section: Discussionmentioning
confidence: 99%
“…All samples from the treatment were adapted for 1 week, then given treatment according to the standard feed of each group. The treatment was conducted for 16 days, and on the 14th day, an injection of S. aureus at a measured by the antibody titer method by agglutination [29]. Determination of the immunomodulatory effect observed on day 17th, blood samples of each rat were taken through a vein in the tail and tissue was taken.…”
Section: Imonomodulator Assay In Vivomentioning
confidence: 99%